Serum neprilysin levels are associated with myocardial stunning after ST-elevation myocardial infarction. (25th November 2020) - Legallois, D; Macquaire, C; Hodzic, A; Allouche, S; El Kouakhi, I; Manrique, A; Milliez, P; Saloux, E; Beygui, F
Abstract: Background/Introduction: Left ventricular remodeling following ST-elevation myocardial infarction (STEMI) is associated with poor outcome. Neprilysin inhibition leads to improved outcome in patients with altered left ventricular ejection fraction (LVEF). Purpose: We aimed to assess the association between serum levels of neprilysin and left ventricular (LV) volumes, function and remodeling in STEMI patients with successful myocardial reperfusion. Methods: Sixty-eight patients were admitted for STEMI and had both plasma neprilysin measurement at baseline and 3D transthoracic echocardiogram at baseline and at follow-up (7 months). We compared 3 groups: a group with a low-level of plasma neprilysin (<125 pg/mL, i.e. the lower limit of detection of the assay, 38 patients) and the two other groups were defined as being below or above the median value of the remaining samples (15 patients each). Results: Median age was 58.5±12.8 years and 56 (82.4%) were men. Median LVEF was 45.0±8.5%. Baseline characteristics were comparable among groups. At baseline there was a non-significant trend towards lower end-diastolic volume (p=0.07) but significantly lower LVEF in the high neprilysin group (46.4±8.3%, 47.1±8.1% and 39.1±6.9%, p<0.01). At follow-up, the magnitude of LVEF increase was significantly more important in the high neprilysin group compared to the other groups (p=0.022 for relative change in LVEF and 6.6±7.3%, 3.6±9.0% and 11.3±8.4%, p=0.031 for absolute change in LVEF) resulting in similar LVEF levels at follow-up between all groups (53.0±8.9%, 50.6±9.7% and 50.4±9.9%, p=0.55). Conclusion(s): Initial high neprilysin levels may identify patients with stunned myocardium early after STEMI, with a recovery of contractility leading to improved LVEF at follow-up. Funding Acknowledgement: Type of funding source: None